DETERMINANTS OF SHARIA BANKING PROFITABILITY: Empirical Studies in Indonesia 2011-2020 - Rizal, Fitra; Rofiqo, Azidni (El-Barka Journal of Islamic Economics and Business, 2020)
This study aims to examine the effect of sharia banking characteristics such as Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), Operating Expenses to Operations Revenue (BOPO) on Return on Assets (ROA). The data used in this study are secondary data obtained from Sharia Banking Statistics published by the Financial Services Authority (OJK) with Purposive Sampling Techniques in 14 Sharia Banks in Indonesia for the period 2011-2020. The analysis technique used is multiple linear regression. The analysis shows that the CAR, NPF, BOPO variables significantly influence ROA, but FDR has no effect on ROA. The predictive ability of 4 independent variables (CAR, FDR, NPF and BOPO) to the dependent variable (ROA) is 86.5%, while 13.5% is influenced by other variables not mentioned in this study.Penelitian ini bertujuan untuk menguji pengaruh karakteristik perbankan syariah seperti Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), Operating Expenses to Operations Revenue (BOPO) terhadap Return on Asset (ROA). Data yang digunakan dalam penelitian ini adalah data sekunder yang diperoleh dari Statistik Perbankan Syariah yang dipublikasikan oleh Otoritas Jasa Keuangan (OJK) dengan Teknik Purposive Sampling di 14 Bank Syariah di Indonesia periode 2011-2020. Teknik analisis yang digunakan adalah regresi linier berganda. Hasil analisis menunjukkan bahwa variabel CAR, NPF, BOPO berpengaruh signifikan  terhadap ROA, tetapi FDR tidak berpengaruh terhadap ROA. Kemampuan prediksi 4 variabel independen (CAR, FDR, NPF dan BOPO) terhadap variabel dependen (ROA) adalah 86,5%, sedangkan 13,5% dipengaruhi oleh variabel lain yang tidak disebutkan dalam penelitian ini.